2021
DOI: 10.48550/arxiv.2109.11005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prospects of SETI by small size optical telescopes

Z. N. Osmanov,
V. I. Berezhiani

Abstract: In the present manuscript we consider the possibility of SETI by the small size (with diameters less than 1 m) optical telescopes. Calculations are performed for parameters of a facility of Abastumani Astrophysical Observatory: AZT-14, Cassegrain Reflector with a parabolic mirror. In particular, we show that the techno-signatures of Type-2.x and Type-3.x civilizations might be detected. It is demonstrated that it is possible to detect as hot megastructures (up to 4000 K) built around main sequence stars and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Osmanov (2021a) concluded that Galactic and extragalactic self-replicating von-Neuman probes might be detectable with FAST. Osmanov & Berezhiani (2021) assessed the capability of 1-meter-scale optical telescope to detect hot megastructures around stars, both via thermal emission and optical variability.…”
Section: Results From Searches (15 Papers)mentioning
confidence: 99%
“…Osmanov (2021a) concluded that Galactic and extragalactic self-replicating von-Neuman probes might be detectable with FAST. Osmanov & Berezhiani (2021) assessed the capability of 1-meter-scale optical telescope to detect hot megastructures around stars, both via thermal emission and optical variability.…”
Section: Results From Searches (15 Papers)mentioning
confidence: 99%